MODEL OF THE FORMATION OF RESEARCH COMPETENCE OF STUDENTS-MATHEMATICIANS OF A PEDAGOGICAL UNIVERSITY - Bakhytkul, Kaskatayeva (International Journal of Research -GRANTHAALAYAH, 2018)
In this article, a model is developed for the formation of the research competence of undergraduate mathematicians at a pedagogical university. Purposeful formation of research competence in the conditions of digitalization, development of theoretical approaches to the use of ICT tools in order to: develop the trainee’s personality by involving the trainee in experimental research, forming cognitive interest is one of the most important goals of higher pedagogical education. The purpose of the study is to develop a model for the formation of research competence of students-mathematicians of a pedagogical university, including the forms, means and methods of its formation; The research uses research methods as a theoretical analysis of domestic and foreign scientific literature on the research problem; observation, generalization; As a result, we determined the essence of research competence and developed a model for the formation of research competence (IC) of mathematics students of a pedagogical university, including the forms, means and methods of its formation; To effectively implement the model for the formation of the research competence of the future mathematics teacher, pedagogical conditions have been created that are of great importance for the formation of the research competence of the mathematics teacher. Formation of the IC was conducted through psychological, informative-cognitive, practical training.